2010
DOI: 10.1371/journal.pone.0010257
|View full text |Cite|
|
Sign up to set email alerts
|

Human Direct Actions May Alter Animal Welfare, a Study on Horses (Equus caballus)

Abstract: BackgroundBack pain is the cause of bad welfare in humans and animals. Although vertebral problems are regularly reported on riding horses, these problems are not always identified nor noticed enough to prevent these horses to be used for work.Methodology/Principal FindingsNineteen horses from two riding centres were submitted to chiropractic examinations performed by an experienced chiropractor and both horses' and riders' postures were observed during a riding lesson. The results show that 74% of horses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
67
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(77 citation statements)
references
References 28 publications
7
67
0
3
Order By: Relevance
“…However, there is also growing evidence that obesity due to over nutrition among horses is increasing (Lesimple et al, 2010;Ireland et al, 2012) and represents a significant detriment to health of equines in a manner similar to that by which it is affecting the human population. Studies have revealed varying prevalences up to 45% in pleasure riding horses in the UK (Wyse et al, 2008).…”
Section: Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is also growing evidence that obesity due to over nutrition among horses is increasing (Lesimple et al, 2010;Ireland et al, 2012) and represents a significant detriment to health of equines in a manner similar to that by which it is affecting the human population. Studies have revealed varying prevalences up to 45% in pleasure riding horses in the UK (Wyse et al, 2008).…”
Section: Parametersmentioning
confidence: 99%
“…Pathological or painful conditions such as lameness, sore mouth, and back pain can arise through injury associated with inadequate housing, management, activities, and equipment (Wyse et al, 2008;Lesimple et al, 2010;McGowan et al, 2010;Murray et al, 2010;Ireland et al, 2012;Lesimple et al, 2012). Lameness was a frequently reported health problem by owners of dressage horses in the study of Murray et al (2010): 33% of the horses were lame at some time during their career.…”
Section: Parametersmentioning
confidence: 99%
“…Although this may seem a constraint for riding centers, keeping horses which work regularly as a group outside work may also favour easier management of horses and riders during lessons. As hierarchy and familiarity are established outside work, much less attention has to be given to the regulation of aggression at work, which may lower the attention to the riders' action and therefore the horses' welfare (Lesimple et al, 2010). This in turn may also be a source of aggression from horses … to humans .…”
Section: Conclusion: Towards Better Practicesmentioning
confidence: 99%
“…A study on how human psychological and physiological state can be perceived by horses was performed in [5] via the study of the heart rate. A more relaxed equine behavior was observed when humans showed positive attitudes toward them [6,7], while an equine increased heart rate was observed when humans were engaged in negative thinking [8]. A nervous mood can be transmitted from humans to horses under handling and riding conditions [9].…”
Section: Introductionmentioning
confidence: 99%
“…The perception of humans by horses seems to be based on experience and repeated interactions, with horses that form a memory of humans that impacts their reactions in subsequent interactions [5]. Hence, previous negative experiences with human contact could lead horses toward a negative emotional reaction [7] or, vice versa, previous positive experience could lead them toward positive feelings with humans [41].…”
Section: Introductionmentioning
confidence: 99%